Modeling total quality management in higher education with case-based reasoning - Jani H.M. (2023)
Total quality management (TQM) is a philosophy and a system for continuously improving the services and products offered to customers through ongoing refinements in response to continuous feedback. With regards to higher education, quality education needs to be emphasized in ensuring progressive intellectual capacity building. Both quality assurance and management are critical in ensuring that higher learning institutions provide better services to their primary customers. The continuous improvement and growth focus of TQM would offer more excitement and challenges to students and lecturers as compared to a "good enough" traditional learning environment. In this paper, elements of an education system that focus on total quality assurance and management are discussed. This paper emphasizes on the mastery learning approach, which is in line with TQM. The learning process contains the following steps: Plan, teach (Do), Check (formative evaluation), revised teaching (Act), and Test (summative evaluation). The two main objectives of using TQM in education, which are to improve learning and to improve cost effectiveness, are emphasized. The paper concludes with a TQM system model that applies genetic algorithm (GA) in case-based reasoning (CBR) that can be used as guidelines to total quality assurance and management in higher education. The combination of CBR and GA will produce a better TQM system model as compared to the one introduced earlier in a previous paper. It is believed that this newly proposed system model is useful in building intellectual capacity in higher education.